Pengaruh Citra Merek dan Kepercayaan terhadap Keputusan Pembelian Tiket Pesawat pada Konsumen Tiket.Com - Wahyuni, Yuyun; Lenti, Norianti (Jurnal Bisnis, Manajemen, dan Akuntansi, 2024)
This research aims to determine the influence of brand image and trust on airline ticket purchasing decisions among tiket.com consumers. The sampling tool used questionnaire media with a sample size of 150 respondents. The data used in this research is primary data. Data collection techniques use questionnaires. The population in this study are people who purchase airplane tickets using tiket.com. Before testing, the research instrument was first tested using validity and reliability tests. The analysis tool uses multiple linear regression tests. Hypothesis testing was carried out using the t test and F test, followed by the Determination Coefficient Test (R2) to determine the contribution of the included variables to the research results. The results of the regression test show that every one unit increase in the independent variable, both brand image and trust, will increase the decision to purchase airplane tickets. Hypothesis testing using the t test and F test gives the results that the two variables have a significant influence on the decision to purchase airplane tickets at the tiket.com company. The coefficient of determination obtained (R^2) was 40.6%, which means that the contribution of the brand image and trust variables to airline ticket purchasing decisions among tiket.com consumers was 40.6%.